Complexing of bacterial lipopolysaccharide with lung surfactant. - Brogden, K A (Infect Immun, 1986)
Lipopolysaccharides (LPS) from Escherichia coli, Salmonella typhi, Klebsiella pneumoniae, Serratia marcescens, or Pseudomonas aeruginosa were mixed with pulmonary surfactant to investigate their in vitro interaction. After 6 h of incubation at 37 degrees C, LPS-surfactant mixtures were examined by sucrose density gradient centrifugation. The E. coli LPS-surfactant mixture was examined by immunoelectron microscopy with protein A-colloidal gold. The binding that occurred between LPS and the surfactant vesicles resulted in a complex with a density higher than the density of the surfactant alone. The protein A-colloidal gold identified LPS in the LPS-surfactant complexes. The toxicity of E. coli LPS was enhanced by complexing with the surfactant when compared with the intraperitoneal injection into CF1 mice, even at a 64:1 ratio of surfactant to LPS. The complexing of LPS and surfactant in the lung may alter the physiologic properties of surfactant that contribute to the physiopathological changes observed with some types of pneumonia. IMAGES: